Copper-Modified Activated Carbons as Adsorbents of NO under Ambient Conditions - Benoit Levasseur; Eugene Gonzalez-Lopez; Teresa J. Bandosz (Adsorption Science & Technology)
Activated carbon was impregnated with a copper salt and the surface of the resulting material then reduced either with hydrazine hydrate or by heat treatment under nitrogen at 925 °C. The adsorption of NO was carried out under dynamic conditions at ambient temperature on the samples obtained. To derive the mechanism of adsorption, the initial material and that exposed to NO were characterized using nitrogen adsorption, thermal analysis and potentiometric titration. The introduction of copper and reduction treatment had very positive effects on the amounts of NO retained on the surface. It is suggested that both copper particles and oxygen-containing groups on the carbon surface contribute to the reactive adsorption. Two different mechanisms are proposed to describe NO adsorption depending on the oxidation state of the copper particles. In the absence of reducing treatment, it is believed that NO is oxidized to NO 2 by copper oxide particles. This NO 2 either reacts with the carbon surface to oxidize it and generate oxygen-containing functional groups or reacts with reduced copper particles. Equally, after surface reduction, the metallic copper could activate oxygen which would then participate in the oxidation of NO into NO 2 . This NO 2 would either chemisorb onto copper in the form of the nitrate or react with the surface oxygen functional groups.